PO86 | Emicizumab in patients with moderate hemophilia A and severe bleeding phenotype: single-center real-world experience (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: The role of prophylaxis in moderate hemophilia A (HA) patients is less clear than in severe HA, given their variable bleeding phenotype. A relevant portion of moderate HA patients may have a severe bleeding phenotype, characterized by frequent hemarthrosis, with a consequent high risk of developing chronic arthropathy. Therefore, this patients’ subgroup has been historically managed with factor VIII (FVIII) prophylaxis. Recently, the HAVEN 6 study has demonstrated the safety and efficacy of emicizumab prophylaxis in moderate/mild hemophilia A patients without inhibitors. In the subgroup of patients with moderate HA and severe bleeding phenotype, a significant reduction of the bleeding rate was observed, leading to the approval of emicizumab prophylaxis in this setting.